2021
DOI: 10.1017/s0022109021000387
|View full text |Cite
|
Sign up to set email alerts
|

Flattening the Illiquidity Curve: Retail Trading During the COVID-19 Lockdown

Abstract: This article studies the impact of retail investors on stock liquidity during the COVID-19 pandemic lockdown in spring 2020. Retail trading exhibits a sharp increase, especially among stocks with high COVID-19–related media coverage. Retail trading attenuated the rise in illiquidity by roughly 40% but less so for high-media-attention stocks. Causality is addressed using the staggered implementation of the stay-at-home advisory across U.S. states. The results highlight that ample free time and access to financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(37 citation statements)
references
References 39 publications
(43 reference statements)
1
29
0
Order By: Relevance
“…A plausible alternative explanation is that COVID-19 served as a salient event that shifted the attention of retail investors away from sustainable investments toward other assets. Consistent with this channel, Ozik, Sadka, and Shen (2021) show that retail trading activity increased sharply during COVID-19 lockdowns, especially among stocks with high COVID-19-related media coverage. We explore this channel in three ways.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…A plausible alternative explanation is that COVID-19 served as a salient event that shifted the attention of retail investors away from sustainable investments toward other assets. Consistent with this channel, Ozik, Sadka, and Shen (2021) show that retail trading activity increased sharply during COVID-19 lockdowns, especially among stocks with high COVID-19-related media coverage. We explore this channel in three ways.…”
Section: Introductionmentioning
confidence: 61%
“…Another potential explanation is that retail investors may have disproportionately shifted their allocation or attention across different types of investments in response to "salient news" regarding COVID-19 or other correlated events. For example, retail investors in ESG mutual funds may have increasingly migrated to directly investing in stocks amid rising interest in retail stock trading (see Ozik et al (2021)). This shift may also be correlated with the magnitude of the impact of COVID-19, partially explaining our findings.…”
Section: Changes In Allocation and Attentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Giglio et al (2021) examined how the pandemic altered the investors’ economic growth and equity returns predictions, and Golubeva (2021) investigated firm-, finance- and country-specific factors’ influence on firm performance during the pandemic. Menkhoff and Schröder (2022), Ozik et al (2021) and Ortmann et al (2020) found a significant increase in retail trading during or after the pandemic. Mattera et al (2021) and Sivaprasad and Mathew (2021) also studied the pandemic’s effect on firm strategy and performance, while Takahashi and Yamada (2021) analyzed the same but focusing on Japan.…”
Section: Introductionmentioning
confidence: 92%
“…Several studies have focused on specific countries. In addition to the number of studies focusing on the US market such as Ozik et al (2021) and Pagano et al (2021), Menkhoff and Schro ¨der (2022) surveyed risky asset ownership in Germany during the COVID-19 shock, finding a tentative decline in April 2020 and a rebound in May 2020. Takahashi and Yamada (2021) examined variables influencing Japanese stock returns during the pandemic period, focusing on ownership structure, global value chains and the ESG rating, and found that enterprises with ESG funds perform better than those without.…”
Section: Introductionmentioning
confidence: 99%